2023
DOI: 10.1177/1179173x231152316
|View full text |Cite
|
Sign up to set email alerts
|

“Appagalo” a Customized Mobile Health Intervention (mHealth) for Smoking Cessation in Women: A Randomized Controlled Trial

Abstract: BACKGROUND Almost 30% of Chilean women report cigarette smoking with important repercussions on their health. OBJECTIVE Design and test a mobile phone intervention for smoking cessation in young women. STUDY DESIGN A mobile application (app) was created using the best available evidence and consumer input. Its effectiveness was assessed through a randomized clinical trial. STUDY PARTICIPANTS Women 18 to 44 years old from middle-class neighborhoods in Santiago, Chile. Inclusion criteria were intention to quit c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Evidence-based mhealth interventions can confirm the efficacy of health promotion programs. Several studies have shown the usefulness of mhealth interventions in preventing high-risk behaviors such as smoking, substance abuse, and alcohol consumption (33)(34)(35)(36). Moreover, Moore et al reported that the smoking abstinence rate in these interventions was generally 1.5 times higher than the control group (37).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-based mhealth interventions can confirm the efficacy of health promotion programs. Several studies have shown the usefulness of mhealth interventions in preventing high-risk behaviors such as smoking, substance abuse, and alcohol consumption (33)(34)(35)(36). Moreover, Moore et al reported that the smoking abstinence rate in these interventions was generally 1.5 times higher than the control group (37).…”
Section: Discussionmentioning
confidence: 99%
“…Smartwatch technology has been developed and tested in interventional smoking cessation studies within the past decade, yet study samples have been small, and more testing is required to improve the accuracy of smoking detection [40][41][42][43]. Similarly, mHealth has been used for smoking cessation and has been found to be effective in the short term [44][45][46][47][48][49][50][51], with little evidence of efficacy in the long term [52]. A systematic review of quit-smoking apps in Android's Play Store and Apple's App Store found high rates of existing irrelevant or nonfunctioning apps and few apps with evidence-based support [53].…”
Section: Overviewmentioning
confidence: 99%